Coastal State Regulation of Bunkering and Ship-to-Ship (STS) Oil Transfer Operations in the EEZ: An Analysis of State Practice and of Coastal State Jurisdiction Under the LOSC. (2nd October 2019) - Testa, David
Abstract : While the United Nations Convention on the Law of the Sea (LOSC) expressly allocates jurisdiction in regard to several activities that are conducted in the exclusive economic zone (EEZ), it does not do so for bunkering and ship-to-ship (STS) oil transfers. This article sheds light on different types of bunkering operations, as well as on the often-overlooked practice of STS oil transfers. It suggests that in the case of bunkering, the allocation of jurisdiction as between coastal and flag states depends on the activity of the vessel being bunkered. In the case of STS oil transfers, it concludes that jurisdictional competence needs to be determined in line with Article 59 of the LOSC. The article also examines relevant state practice and contends that the LOSC's ambiguity is no license to unfettered coastal state regulation.